Sexual concerns of cardiac patients: A psychometric analysis. Issue 6 (26th March 2014) - Mosack, Victoria; Hill, Twyla J; Steinke, Elaine E
Abstract : The primary aim of this study was to evaluate the psychometric properties of the Steinke Sexual Concerns Inventory—General Cardiac Version (SSCI‐GCV) and to examine its use across multiple cardiac diagnoses. A sub‐analysis of a cross‐sectional sample of 205 cardiac patients from the central USA was completed. Our analyses yielded promising evidence that the SSCI‐GCV is a reliable (Cronbach's alpha = 0.86) and valid measure of sexual concerns and supported three subscales for this 11‐item instrument. Further means testing suggested that participants with a diagnosis of stroke or kidney disease reported more sexual concerns than those without such diagnoses, but differences were not found for any specific cardiac health problem or intervention. These findings support the use of the SSCI‐GCV as a brief and easily administered instrument that can be used to broadly assess sexual concerns in cardiac populations and to inform sexual counselling of cardiac patients in practice.